The Writing on the…Desk: Desktop Graffiti as Unobtrusive Measure of Campus Climate Before and After the Virginia Tech Massacre. Issue 3 (3rd March 2020) - Ball, Daisy
ABSTRACT: Graffiti has long been a topic of study for social scientists. The unique medium of graffiti allows the writer relative autonomy, and may offer insight about deviance in society. The present study employs desktop graffiti as an unobtrusive measure of campus climate at Virginia Tech, the site of the deadliest school shooting in U.S. history. Using the methodology of content analysis, data in the form of desktop graffiti – student-authored graffiti on student desktops – collected prior to the 2007 mass shooting was compared to data collected one semester and one year following the massacre. A total of 1, 065 desktops were studied, resulting in 7, 004 pieces of graffiti analyzed. The first round of data serves as a baseline measurement, to which themes uncovered in subsequent rounds are compared. What emerges is an unobtrusively painted portrait of campus climate before and after tragic, and highly visible, events. Implications for the study of campus climate, and for campuses recovering from tragic events, are considered, as are the study's limitations.